Synthesis of Azaheterocyclic Vinylphosphonates by Ring‐Closing Metathesis. Issue 18 (5th May 2013) - Garzon, Cécile; Attolini, Mireille; Maffei, Michel
Abstract: The title compounds were synthesized by ruthenium‐catalyzed ring‐closing metathesis of N ‐tosyl‐ N ‐(ω‐alkenyl)aminomethylvinyl phosphonates, which were obtained from N ‐(ω‐alkenyl)‐ N ‐tosylamides. These compounds, in turn, were prepared from unsaturated alcohols through the Mitsunobu reaction. This methodology gives access to five‐ and six‐membered ring compounds. Additionally, chiral phosphonates can be obtained easily. Abstract : Organocatalysis and ring‐closing metathesis enable a two‐step synthesis of azaheterocyclic vinylphosphonates, giving access to five‐ and six‐membered ring compounds. The required (ω‐alkenyl) p ‐toluenesulfonamides were obtained through the Mitsunobu reaction, which allows the synthesis of chiral phosphonates.